Entanglement Area Law in Disordered Free Fermion Anderson Model in One, Two, and Three Dimensions - Mohammad Pouranvari; Yuhui Zhang; Kun Yang (Advances in Condensed Matter Physics)
We calculate numerically the entanglement entropy of free fermion ground states in one-, two-, and three-dimensional Anderson models and find that it obeys the area law as long as the linear size of the subsystem is sufficiently larger than the mean free path. This result holds in the metallic phase of the three-dimensional Anderson model, where the mean free path is finite although the localization length is infinite. Relation between the present results and earlier ones on area law violation in special one-dimensional models that support metallic phases is discussed.